PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP PRAKTIK MANAJEMEN LABAPADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Nurlina Nurlina; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to examine whether the corporate governance mechanism affect the practice of earnings management in the Islamic banking industry in Indonesia. Internal governance mechanisms can supervise manager actions more effectively than external governance mechanisms. Therefore, this study focuses on internal governance mechanisms. The method of data collection in this study is documentation. The sample of this research is Sharia Commercial Banks in Indonesia which are determined by applying the purposive sampling method. After applying the method, there are 11 Sharia Commercial Banks that meet the criteria as research samples. The analytical method used in this study is panel regression with FEM (Fixed Effect Model) in the first stage and REM (Random Effect Model) in the second stage.The results of this study reveal that the size of the Board of Commissioners, the size of the Audit Committee, and the size of the SSB (Sharia Supervisory Board) are significant and positively affect the earnings management practices. In addition, this study successfully confirmed that the SSB competency is significant and negatively affect the earnings management practices. However, the number of Board of Commissioners meetings, the independence of the Board of Commissioners, the number of Audit Committee meetings, and the number of SSB meetings were not proven to affect earnings management practices.